English Lexis in the Documents of the European Union – A Corpus-Based Exploratory Study - Trebits, Anna (Working Papers in Language Pedagogy, 2008)
The present study aims to explore the characteristics of lexical elements in English language documents of the European Union (EU). As the EU is involved in a wide range of activities, the documents related to it exhibit features of texts written for legal, business, political and other specific purposes. The aim of this corpus-based research is to identify and describe the lexical elements whose mastery is indispensable for those who wish to work in cooperation with or inside a European institution. An EU English Corpus consisting of approximately 200,000 words was built using texts which are representative of the various fields of activities of the EU. The analysis uncovered the most frequent lexical elements and collocation patterns as well as their most common uses and senses in this particular variety of the English language. This article discusses and demonstrates the methods of analysis through the detailed presentation of three of the most frequently occurring lexical elements. The pedagogical relevance of the study is that its findings can be directly used for the development of special English language course books and supplementary materials for EU and International Relations courses.